Anogenital Verru and Sexual Abuse in Childhood Review - Demirkıran, Dua Sumeyra; Arslan, Muhammet Mustafa (The Bulletin of Legal Medicine, 2014)
The presence of sexually transmitted diseases at anogenital region of children is an evidence of sexually abuse. Human papilloma virus (HPV) which affects 80% of adults is considered to be the most common sexually transmitted disease. The warts which were formed in children secondary to HPV, may be an indicator of sexual abuse. Following a review of the literature about the children with anogenital warts (AGW), we aimed at sharing the suggestions for the approach in this group of patients, from the forensic point of view.It has also been proved scientifically that HPV may be transmitted in some other ways else than sexual abuse. Therefore in children with AGW, the prejudicied consideration as having formed secondary to sexual abuse should be broken. Children and their families must not be misinformed in order to avoid the psychological stress of having formed secondary to sexual abuse. These cases should be evaluated by a multidisciplinary approach and may only be considered as a forensic case after having a clear judgement about way of sexually transmission.Keywords: anogenital verru, transmission, sexual abuse, HPV
Keywords: anogenital verru; transmission; sexual abuse; hpv